REFERENCING AND COHERENCE STRATEGIES IN THE TOP-SCORING ESSAYS OF THE 2021 ENEM: A TEXTUAL ANALYSIS (PERcursos Linguísticos, 2025)
This study aims to analyze the role of referencing processes in argumentative essays that achieved a perfect score (1000) in the 2021 ENEM and their implications for teaching writing. For theoretical support, we adopt the sociocognitive conception of language, understanding reference as a complex process that goes beyond textual expressions, requiring a sociocognitive effort to construct discursive elements. The analysis is based on theories by Salomão (1999), Marcuschi (2007), Koch and Cunha-Lima (2011), among others, who view the text as a communicative event and referencing as a discursive stabilization process. The research examined an essay from high school students who received the maximum score in the 2021 ENEM, aiming to contribute to studies on referencing and to highlight the changes and new meanings in the essays. In conclusion, we observe that argumentative-essay writing broadens contexts and reconfigures meanings by incorporating diverse readings.
Keywords: Referencing; Enem; Textual analysis